LEGAL ANALYSIS OF LEGAL PROTECTION FOR GIG ECONOMY WORKERS IN THE INDONESIAN EMPLOYMENT SYSTEM - Masitah Pohan; Rahmayanti (PT. Radja Intercontinental Publishing, 2026)
The development of digital technology has given rise to the gig economy phenomenon, transforming employment patterns within the Indonesian labor system. This work model is characterized by high flexibility and partnership-based employment relationships through digital platforms. However, despite this flexibility, gig workers face various legal challenges, particularly related to unclear employment status and minimal legal protection for basic workers' rights. This study aims to analyze legal protection for gig economy workers within the Indonesian labor system and to assess the suitability of existing regulations to platform-based work practices. The research method used is normative legal research with a statutory approach and a conceptual approach. The legal materials used include legislation, legal literature, and doctrines relevant to employment and the gig economy. The analysis was conducted qualitatively to identify gaps between applicable legal norms and the reality of practice on the ground. The results indicate that legal protection for gig economy workers in Indonesia is suboptimal. This is due to the absence of specific regulations that explicitly regulate the status and rights of gig workers within the labor system. Existing regulations still focus on conventional employment relationships, thus preventing gig workers classified as partners from receiving protections such as social security, a living wage, and job security. Furthermore, dispute resolution mechanisms between workers and platforms have not been comprehensively regulated.